The Effect of Controlled-Release Carvacrol on Safety and Quality of Blueberries Stored in Perforated Packaging - Sun, Xiuxiu (Foods, 2021)
The objective of this research was to evaluate the use of a controlled-release carvacrol powder to delay storage decay and maintain the safety of blueberries. The controlled-release carvacrol powder was a microcapsule of carvacrol (11% (w/w) active carvacrol) surrounded by a pectin/sodium alginate matrix. The microcapsules were packed in an air-permeable pouch, and then attached to the top of a clamshell filled with blueberries. The blueberries, inoculated with Escherichia coli or Colletotrichum acutatum, or non-inoculated control, were monitored for microbial growth and quality for 10 days at 10 °C and 5 days at 20 °C. Three treatments were compared: controlled-release microencapsulated carvacrol, non-encapsulated carvacrol, and control. The results showed that both the microencapsulated carvacrol and the non-encapsulated carvacrol treatments significantly reduced the populations of yeast and mold, and of E. coli and mesophilic aerobic bacteria. The microencapsulated carvacrol treated berries retained better quality due to significantly lower weight loss than control after 10 days at 10 °C. Sensory panelists found that the microencapsulated carvacrol berries had significantly higher overall blueberry flavor and lower discernible off-flavor in comparison with the non-encapsulated treatment after 3 days at 20 °C. The fruit internal quality, including total soluble solids content (SSC), and titratable acidity (TA), was not significantly affected by any treatment. These results indicate that pectin/sodium alginate controlled-release microencapsulated carvacrol can be used for the preservation of blueberries or other small fruit.